2013
DOI: 10.1021/jp4032749
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Impurity Location and Binding in Heavily Doped Semiconductor Nanocrystals: The Case of Cu in InAs Nanocrystals

Abstract: The doping of colloidal semiconductor nanocrystals (NCs) presents an additional knob beyond size and shape for controlling the electronic properties. An important problem for doping with aliovalent elements is associated with resolving the location of the dopant and its structural surrounding within small NCs, an issue directly connected with self-purification. Here we used a postsynthesis diffusion-based doping method for introducing Cu impurities into InAs quantum dots. X-ray absorption fine structure (XAFS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 38 publications
(79 citation statements)
references
References 54 publications
3
73
2
1
Order By: Relevance
“…38 Indeed, p-type behavior was observed by us for Ag in InAs, 31 consistent with substitutional doping. Additional support for this model is gained from the Ag K-edge EXAFS data behavior (Figure 6aÀc), dominated by the AgÀAs contribution, as also evidenced by the quantitative data analysis.…”
Section: Articlementioning
confidence: 76%
See 1 more Smart Citation
“…38 Indeed, p-type behavior was observed by us for Ag in InAs, 31 consistent with substitutional doping. Additional support for this model is gained from the Ag K-edge EXAFS data behavior (Figure 6aÀc), dominated by the AgÀAs contribution, as also evidenced by the quantitative data analysis.…”
Section: Articlementioning
confidence: 76%
“…In a following work, we have reported on the detailed characterization of Cu doping of InAs NCs, using advanced X-ray absorption fine structure (XAFS) spectroscopy to establish the location of the impurity and its electronic state within the NC as a function of the impurity to NC ratio in the reaction solution. 38 We found that the diffusion of Cu impurities into the NC lattice is favored and results in an energetically stable system. Furthermore, we identified the impurity site, determining that the Cu impurities occupy only hexagonal-interstitial sites throughout the lattice for a very wide range of impurity concentrations.…”
mentioning
confidence: 79%
“…Breifely, the QDs were reacted with calculated volumes of a solution containing the appropriate surface ligands and the 8 plasma (ICP) measurements were used to correlate between the above solution values and the number of Cu atoms within the QD ( Figure S1 in the SIO). 2,11 Close investigation reveals a slight red-shift of the first exciton (~5meV) for Cu doping levels up to 125 Cu atoms/QD; this is related to the initial appearance of doped states situated slightly below the QD conduction band.…”
Section: Cu Doping Of Inas Quantum Dotsmentioning
confidence: 96%
“…The interstitial location of Cu + impurities was later verified by X-ray absorption fine structure (XAFS) spectroscopy measurements and DFT calculations. 85 In contrast, Au 3+ acts as an isovalent substitution for In 3+ , perturbing the bandedge structure, but not appreciably doping the particles. While isovalent doping does not effect equilibrium carrier concentrations, the midgap states that it induces can sometimes be utilized as a charge transfer rely or optically active site, as in the case of Mn 2+ in CdS.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%